2021
DOI: 10.4314/njt.v40i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of emulsion paint wastewater using Azolla Pinnata, Eichhornia Crassipes and Lemna Minor

Abstract: The use of three macrophytes namely Azolla pinnata, Eichhornia crassipes and Lemna minor for the phytoremediation of emulsion paint wastewater was investigated. Samples of the paint wastewater and test plants were collected and analyzed for physicochemical characteristics and heavy metal concentrations before and after phytoremediation for six weeks. The TDS of the treated wastewater was reduced by over 80.0% by each of the test plants while the TSS increased as a result of debris from wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The increase in the BOD/COD ratio indicated that the processing plant produces treated leachate to be more biodegradable. The increase in the BOD/COD ratio through the processing of these plants is in line with the results of previous phytoremediation studies (Echiegu et al 2021;Hamidah and Widiyanti 2021). In terms of contaminant elimination, the results were comparable to the performance of leachate treatment using membrane filters and anaerobic membrane bioreactors (Abuabdou et al 2022;2020).…”
Section: Organic Removal and Plantssupporting
confidence: 91%
“…The increase in the BOD/COD ratio indicated that the processing plant produces treated leachate to be more biodegradable. The increase in the BOD/COD ratio through the processing of these plants is in line with the results of previous phytoremediation studies (Echiegu et al 2021;Hamidah and Widiyanti 2021). In terms of contaminant elimination, the results were comparable to the performance of leachate treatment using membrane filters and anaerobic membrane bioreactors (Abuabdou et al 2022;2020).…”
Section: Organic Removal and Plantssupporting
confidence: 91%